CATCH ANALYSIS OF TREVALLY (Carangoides spp. RUPPELL, 1830) AT KANDANGSEMANGKON SMALL LANDING SITE, LAMONGAN, EAST JAVA - Harlyan, Ledhyane Ika; Zahra, Afifah; Lelono, Tri Djoko (Directorate of Research and Community Service (DRPM), 2023)
Fisheries data statistics play an important role in fisheries management. The data collection might be provided in landing sites. However, not all landing sites can provide the fisheries data. Kandangsemangkon small landing site is an unreported landing site that land various economically important species, one of species is Trevally fishery. The purposes of this study were to identify the species landed, determine the categorization of species supporting the landed trevally fishery and determine the trevally fishing area and the volume of trevally production that was not recorded or reported at Kandangsemangkon Small Landing Site. The data collection method of this study is by descriptive survey method, which are by taking primary and secondary data. The primary data collection was carried out by interviewing fishermen regarding the species of catch landed and the trevally fishing area, and observing the research location. The secondary data used was the production data of trevally landed at Brondong Archipelago Fishing Port. The results of this study are there were types of target species, secondary species, primary species and there is not endangered, threatened and protected species were found. The trevally fishing grounds are generally in WPPNRI 712 and 713. The volume of unrecorded and unreported production was 46.70%, and did not contribute to the fisheries statistics of Lamongan, East Java.